Lamotrigine treatment of pathologic skin picking: an open-label study - Grant, Jon E; Odlaug, Brian L; Kim, Suck Won (The journal of clinical psychiatry, 2007)
Although pathologic skin picking is a relatively common behavior, treatment data are limited. We hypothesized that lamotrigine would reduce the symptoms of pathologic skin picking. 24 subjects (19 women [79.2%]; mean +/-SD age = 34.1 +/- 12.2 years) with pathologic skin picking (based on DSM-IV criteria for other impulse control disorders) were treated in a 12-week open-label trial of lamotrigine as mono-therapy. Lamotrigine dosing ranged from 25 mg every other day to 300 mg/day. The primary outcome measure was time per day spent picking. Subjects were also assessed with measures examining the symptoms of pathologic skin picking and psychosocial functioning. Data were collected from January 15, 2006, to September 18, 2006. Mean (SD) time per day spent picking decreased from 118.1 (130.0) to 59.9 (115.2) minutes (p < .001). Sixteen subjects (66.7%) were considered either "very much improved" or "much improved" in terms of skin picking symptoms. Seven subjects (29.2%) reported no picking at study endpoint. Significant improvement was seen on scales assessing the symptoms of pathologic skin picking (p = .001) and social functioning (p = .002). Mean time to response (i.e., when the subject was much or very much improved) was 8 weeks, which corresponded to a lamotrigine dose of 200 mg/day. Lamotrigine was associated with improvements in two thirds of subjects with pathologic skin picking. Placebo-controlled, double-blind studies are needed to evaluate further the safety, tolerability, and efficacy of lamotrigine in the treatment of this problematic behavior. ClinicalTrials.gov identifier NCT00269594 (http://www.clinicaltrials.gov).